Changes in the height of the pollution boundary layer and their meteorological effects on the distribution of surface ozone concentrations - Liu, Liangke; Zhang, Xiaoye; Wang, Jizhi; Yang, Yuanqin; Jia, Wenxing; Zhong, Junting; Jiang, Xiaofe; Wang, Yaqiang (Frontiers in Environmental Science, 2022)
Focusing on the key air pollution regions in China, by using hourly automatic weather data, ground-based and high-altitude meteorological sounding data, and near-surface O3 monitoring data, here we try to quantify the relationship between boundary layer meteorological condition and near-surface O3 concentrations. The key meteorological element include changes in solar zenith angle, cloud height, atmospheric condensation rate, and the associated change in the boundary layer height. We also try to better understand the mechanisms by which meteorological conditions affect near-surface O3 concentrations, and it is found that the exponential increase in near-surface O3 concentrations after sunrise (called O3 concentration entrainment, EZ) is meaningfully associated with exceeding the threshold of a water vapor condensation rate (fc) that is often closely linked to a significant rise in the pollution boundary layer, and that this proves to be diagnostically important for understanding the O3 EZ. Diurnal variations in solar zenith angle and boundary layer height are key meteorological factors influencing the large increase in near-surface O3 concentration entrainment.